2007
DOI: 10.1080/02705060.2007.9664820
|View full text |Cite
|
Sign up to set email alerts
|

Prey Selection of Subyearling Atlantic Salmon and Rainbow Trout Coexisting in a Natural Stream

Abstract: Atlantic salmon (Salmo salar) and rainbow trout (OncovCiynchus mykiss) are similar ecologically but share no coevolutionary histoly favoring the evolution of niche-partitioning mechanisms. Therefore, interspecifi c competition may occur as each species becomes naturalized throughout the other's native range. As a first step towards investigating competitive interactions, we tested hypotheses regarding prey selection in allopatric and sympatric populations of Atlantic salmon and rainbow trout in a natural strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…On the other hand, Pedley and Jones (1978) stated that interspecific competition between S. salar and S. trutta was only significant during the summer months when food was abundant. Our results, using the Schoener's index, suggest a remarkable similarity in prey utilization patterns between species as previously stated by other researchers (Gibson & Cunjak 1986;Coghlan et al 2007). However, the high overlap values found in the present study might not indicate competition, for two reasons.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, Pedley and Jones (1978) stated that interspecific competition between S. salar and S. trutta was only significant during the summer months when food was abundant. Our results, using the Schoener's index, suggest a remarkable similarity in prey utilization patterns between species as previously stated by other researchers (Gibson & Cunjak 1986;Coghlan et al 2007). However, the high overlap values found in the present study might not indicate competition, for two reasons.…”
Section: Discussionsupporting
confidence: 81%
“…Several authors have found that diet overlap is high between Atlantic salmon and other salmonids species in sympatry (Gibson & Cunjak 1986;Coghlan et al 2007). In a previous study in Spain, Suárez et al (1988) found significant interspecific differences in the diet between S. salar and S. trutta in May and November, although they did not find differences in April and July.…”
Section: Discussionmentioning
confidence: 98%
“…for interspecific competition (Coghlan et al, 2007). Our results show that in the season with a high feeding intensity (reflected in high stomach fullness), there was a lower dietary overlap in comparison with the periods when feeding intensity declined.…”
Section: Discussionmentioning
confidence: 64%
“…Diets containing more terrestrial invertebrates in one of the two coexisting species have been reported by several studies on related species of salmonids (Coghlan et al, 2007;McHugh et al, 2008;Wilson et al, 2014). Such shifts may be caused by differences in prey utilization, as well as by changes in habitat use when the dominant species outcompetes subordinates from favourable feeding positions (Blanchet et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation